Recovery and concentration of ammonia from return liquor to promote enhanced CO2 absorption and simultaneous ammonium bicarbonate crystallisation during biogas upgrading in a hollow fibre membrane contactor - Bavarella, Salvatore; Hermassi, Mehrez; Brookes, Adam; Moore, Andrew; Vale, Peter C. J.; Moon, Ilshik S.; Pidou, Marc; McAdam, Ewan (Elsevier, 2020)
In this study, thermal desorption was developed to separate and concentrate ammonia from return liquor, for use as a chemical absorbent in biogas upgrading, providing process intensification and the production of crystalline ammonium bicarbonate as the final reaction product. Applying modest temperature (50°C) in thermal desorption suppressed water vapour pressure and increased selective transport for ammonia from return liquor (0.11MNH3) yielding a concentrated condensate (up to 1.7MNH3). Rectification was modelled through second-stage thermal processing, where higher initial ammonia concentration from the first stage increased mass transfer and delivered a saturated ammonia solution (6.4MNH3), which was sufficient to provide chemically enhanced CO2 separation and the simultaneous initiation of ammonium bicarbonate crystallisation, in a hollow fibre membrane contactor. Condensate recovered from return liquor exhibited a reduction in surface tension. We propose this is due to the stratification of surface active agents at the air-liquid interface during primary-stage thermal desorption which carried over into the condensate, ‘salting’ out CO2 and lowering the kinetic trajectory of absorption. However, crystal induction (the onset of nucleation) was comparable in both synthetic and thermally recovered condensates, indicating the thermodynamics of crystallisation to be unaffected by the recovered condensate. The membrane was evidenced to promote heterogeneous primary nucleation, and the reduction in the recovered condensate surface tension was shown to exacerbate nucleation rate, due to the reduction in activation energy. X-ray diffraction of the crystals formed, showed the product to be ammonium bicarbonate, demonstrating that thermal desorption eliminates cation competition (e.g. Ca2+) to guarantee the formation of the preferred crystalline reaction product. This study identifies an important synergy between thermal desorption and membrane contactor technology that delivers biogas upgrading, ammonia removal from wastewater and resource recovery in a complimentary process.
Keywords: membrane contactor; Biogas; ammonia return liquor; precipitation; thermal stripping; crystallisation